Exercising responsible leadership in a Singapore context. Issue 1 (12th October 2017) - Koh, Carolyn; Fernando, Mario; Spedding, Trevor
Abstract : Purpose: The purpose of this paper is to explore the western developed notion of responsible leadership (RL) from a Singapore context. Design/methodology/approach: Following the qualitative research tradition, face-to-face interviews with 20 influential Singaporean leaders were developed into case studies. Grounded theory methodology was applied to identify similarities and differences within and across cases. Findings: The findings reveal that the interviewed Singaporean leaders projected traits and values consistent with western definitions of responsible and effective leadership. Findings also suggest that contextual factors such as national culture and the ethos of the nation as well as leaders' relational intelligence influence RL. These factors also help responsible leaders to better manage the tension between responsible and effective leadership. Research limitations/implications: The small and geographically bound sample size makes it difficult to generalise the findings of this study. As in other ethics studies, interviewees' desire to present a socially desirable image of themselves could be high in this study. Finally, the methods and analytical techniques applied may be biased and be influenced by the purposive selection of the participants. Practical implications: Singaporean business leaders may need to consider the importance of retaining and developing the national culture and ethos of the nation, since these are the factors that have been identified in this study as key to influencing RL. Originality/value: This study identifies the factors that influence RL from a Singapore context. It extends the understanding of the mostly western-based multi-level theory of RL.